DIABETES RISK SCORE OF STAFF OF AN URBAN MISSION HOSPITAL IN NIGERIA - M, Dankyau; Arj, Shu'aibu; Ae, Oyebanji; O, Mamven (International Journal of Clinical and Biomedical Research, 2015)
Background: Diabetes mellitus is a major global health problem which in hospital staff poses a major stress and can lead to migration away from health related posts. Certain features of health work e.g. long hours, shifts and uncertain break times increase the risk for hospital staff. It is critical to predict chronic conditions like diabetes mellitus that have a definable onset in adults so that morbidity and mortality can be mitigated through early recognition and treatment. Aims: To determine the diabetes risk score of health workers in an urban hospital and the associated risk factors. Methods and Materials: A correlational cross sectional survey of staff was conducted and diabetes risk was determined using a modified form of the Finnish Diabetes Risk Score questionnaire. Results and Conclusions: A total of 220 staff representing a response rate of 69.8% completed the study. The mean age was 41.6±9.88, Median duration of employment was 7.2years with a range of (0-37). Majority (66.4%) were in the 25-44 years age group, and most were female (66.4%) and married (70.5%). Mean BMI was 26.62±4.85. The mean Diabetes Risk score for the entire study group was 7.43±4.46 with a median score of 7 and a range of 0-19. About 40.5% had slightly elevated risk, 14.5% had moderate risk, and 5% had high risk. Female gender (AOR 0.17, 95% CI 0.09-0.33), and duration of employment (AOR 2.27, 95% CI 1.18-4.37) were significant predictors of higher diabetic risk score category. KEYWORDS: Type 2 Diabetes mellitus; Diabetes risk; Risk score; Health workforce.